Manipulation of the response of human endothelial colony-forming cells by focal adhesion assembly using gradient nanopattern plates. (January 2018) - Cui, Long-Hui; Joo, Hyung Joon; Kim, Dae Hwan; Seo, Ha-Rim; Kim, Jung Suk; Choi, Seung-Cheol; Huang, Li-Hua; Na, Ji Eun; Lim, I-Rang; Kim, Jong-Ho; Rhyu, Im Joo; Hong, Soon Jun; et al.
Graphical abstract: Abstract: Nanotopography plays a pivotal role in the regulation of cellular responses. Nonetheless, little is known about how the gradient size of nanostructural stimuli alters the responses of endothelial progenitor cells without chemical factors. Herein, the fabrication of gradient nanopattern plates intended to mimic microenvironment nanotopography is described. The gradient nanopattern plates consist of nanopillars of increasing diameter ranges [120–200 nm (GP 120/200), 200–280 nm (GP 200/280), and 280–360 nm (GP 280/360)] that were used to screen the responses of human endothelial colony-forming cells (hECFCs). Nanopillars with a smaller nanopillar diameter caused the cell area and perimeter of hECFCs to decrease and their filopodial outgrowth to increase. The structure of vinculin (a focal adhesion marker in hECFCs) was also modulated by nanostructural stimuli of the gradient nanopattern plates. Moreover, Rho-associated protein kinase (ROCK) gene expression was significantly higher in hECFCs cultured on GP 120/200 than in those on flat plates (no nanopillars), and ROCK suppression impaired the nanostructural-stimuli-induced vinculin assembly. These results suggest that the gradient nanopattern plates generate size-specific nanostructural stimuli suitable for manipulation of the response of hECFCs, in a process dependent on ROCK signaling. This is the first evidence of size-specific nanostructure-sensing behavior of hECFCs. Significance: Nano feature surfaces are of growing interest as materials for a controlled response of various cells. In this study, we successfully fabricated gradient nanopattern plates to manipulate the response of blood-derived hECFCs without any chemical stimulation. Interestingly, we find that the sensitive nanopillar size for manipulation of hECFCs is range between 120 nm and 200 nm, which decreased the area and increased the filopodial outgrowth of hECFCs. Furthermore, we only modulate the nanopillar size to increase ROCK expression can be an attractive method for modulating the cytoskeletal integrity and focal adhesion of hECFCs.